Structural Dissection of the First Events Following Membrane Binding of the Islet Amyloid Polypeptide - Khemtemourian, Lucie; Fatafta, Hebah; Davion, Benoit; Lecomte, Sophie; Castano, Sabine; Strodel, Birgit (Frontiers in Molecular Biosciences, 2022)
The islet amyloid polypeptide (IAPP) is the main constituent of the amyloid fibrils found in the pancreas of type 2 diabetes patients. The aggregation of IAPP is known to cause cell death, where the cell membrane plays a dual role: being a catalyst of IAPP aggregation and being the target of IAPP toxicity. Using FTIR spectroscopy, transmission electron microscopy, and molecular dynamics simulations we investigate the very first molecular steps following IAPP binding to a lipid membrane. In particular, we assess the combined effects of the charge state of amino-acid residue 18 and the IAPP-membrane interactions on the structures of monomeric and aggregated IAPP. Distinct IAPP-membrane interaction modes for the various IAPP variants are revealed. Membrane binding causes IAPP to fold into an amphipathic α-helix, which in the case of H18K- and H18R-IAPP readily moves beyond the headgroup region. For all IAPP variants but H18E-IAPP, the membrane-bound helix is an intermediate on the way to amyloid aggregation, while H18E-IAPP remains in a stable helical conformation. The fibrillar aggregates of wild-type IAPP and H18K-IAPP are dominated by an antiparallel β-sheet conformation, while H18R- and H18A-IAPP exhibit both antiparallel and parallel β-sheets as well as amorphous aggregates. Our results emphasize the decisive role of residue 18 for the structure and membrane interaction of IAPP. This residue is thus a good therapeutic target for destabilizing membrane-bound IAPP fibrils to inhibit their toxic actions.